Exploration of a 14-3-3 PPI Pocket by Covalent Fragments as Stabilizers - Sijbesma, Eline; Hallenbeck, Kenneth K; Andrei, Sebastian A; Rust, Reanne R; Adriaans, Joris M C; Brunsveld, Luc; Arkin, Michelle R; Ottmann, Christian (ACS medicinal chemistry letters, 2021)
The systematic discovery of functional fragments binding to the composite interface of protein complexes is a first critical step for the development of orthosteric stabilizers of protein-protein interactions (PPIs). We have previously shown that disulfide trapping successfully yielded covalent stabilizers for the PPI of 14-3-3 with the estrogen receptor ERα. Here we provide an assessment of the composite PPI target pocket and the molecular characteristics of various fragments binding to a specific subpocket. Evaluating structure-activity relationships highlights the basic principles for PPI stabilization by these covalent fragments that engage a relatively large and exposed binding pocket at the protein/peptide interface with a "molecular glue" mode of action.The systematic discovery of functional fragments binding to the composite interface of protein complexes is a first critical step for the development of orthosteric stabilizers of protein-protein interactions (PPIs). We have previously shown that disulfide trapping successfully yielded covalent stabilizers for the PPI of 14-3-3 with the estrogen receptor ERα. Here we provide an assessment of the composite PPI target pocket and the molecular characteristics of various fragments binding to a specific subpocket. Evaluating structure-activity relationships highlights the basic principles for PPI stabilization by these covalent fragments that engage a relatively large and exposed binding pocket at the protein/peptide interface with a "molecular glue" mode of action.